2020
DOI: 10.4055/cios19145
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Stress Distribution in Flat and Elevated-Rim Polyethylene Acetabular Liners

Abstract: Unlike in cemented total hip arthroplasty (THA), several types of polyethylene liners can be used in cementless THA. Selection of the appropriate polyethylene liner affects the long-term stability after THA. 1,2) One of the main causes for revision surgery is postoperative dislocation, and the use of elevated polyethylene liners can effectively correct the inclination of metal cups, thereby preventing future dislocations. In cementless THA revision, there are some cases where the metal cup has no looseness, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“… 27) In addition, we speculate that the liner rim elevated over the margin of the acetabular cup might increase the risk of impingement with the stem trunnion damaging the locking mechanism, particularly in young, active Asian men with a cultural habit of squatting. 28) …”
Section: Discussionmentioning
confidence: 99%
“… 27) In addition, we speculate that the liner rim elevated over the margin of the acetabular cup might increase the risk of impingement with the stem trunnion damaging the locking mechanism, particularly in young, active Asian men with a cultural habit of squatting. 28) …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stainless steel has a modulus of roughly 200 GPa, which is significantly more than bone [16] having a modulus in the range of 11-20 GPa. Materials and their properties considered in this study are [21], [22]:…”
Section: Stainless Steelmentioning
confidence: 99%
“…The design and assembly are done in the Fusion 360 software. Acetabular shell has an outside diameter of 52 mm and an inside diameter of 38 mm, an outer diameter of both flat and elevated liner is considered as 28 mm and outer diameter as 38 mm, the elevation of the elevated liner is kept as 10° [21]. The diameter of the femoral head is 28 mm, and the length of the femoral stem is taken as 120 mm [22].…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The average intramedullary canal diameter of the humerus is 14.5 mm(range : 9.4 ~ 20.5 mm) 9 , while the average diameter of the medullary cavity of the distal shaft of the radius is 6.7 mm(range : 6.1 ~ 7.3 mm) and the minimum diameter of the ulna medullary cavity is 4.2 mm(range : 2 ~ 6.7 mm). 10,11 In a review of the literature, no biomechanical study about osseointegrated implants for the trans-radial amputee was found. Because major upper-extremity amputees account for only 8% of the 1.5 million individuals living with limb loss 3 and upper-extremity loss does not affect weight-bearing, 11 therefore, the importance of upper-extremity amputation is lowered.…”
Section: Introductionmentioning
confidence: 99%